Pengaruh Pengembangan Karir Terhadap Loyalitas Karyawan Divisi Rantai Pasok PT.PINDAD Bandung - Safitri, Safitri; Sudartono, Tris (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
This research was conducted to determine the effect of career development on employee loyalty in the Supply Chain Division of PT PINDAD Bandung. The research method used in this study is quantitative method. Data obtained for this study by distributing questionnaires with 20 questions to 37 respondents. Data processing using SPSS V25. With the results of the Coefficient of Determination Test research stated that career development has an influence of 45.6% on employee loyalty and 54.4% influenced by other factors. While the results of the Simple Linear Regression Analysis Test areVariable Y Employee Loyalty has a fixed value of 16.533 and the regression coefficient value of Variable X Career Development is 0.706, meaning that if variable X Career Development increases by 1 (one) value, then Variable Y Employee Loyalty increases by 0.706. Then the company needs to pay attention to employees who have underdeveloped careers, because it can affect employee loyalty to the company.